KEBIJAKAN KURIKULUM MERDEKA BELAJAR KAMPUS MERDEKA (MBKM) DI PERGURUAN TINGGI - Shaffan Waliudin, Achmad; Aziz, Abdul; Zaenul Fitri, Agus (SKILLS : Jurnal Riset dan Studi Manajemen Pendidikan Islam, 2023)
Currently, changes are taking place very quickly following the flow of globalization and technological advances. Therefore, education has an important role in preparing Human Resources (HR) who have various skills so they can face dynamic life. The Independent Campus Learning Policy (MBKM) exists to improve the competency of graduates from tertiary institutions in the form of soft skills and hard skills so that they can adapt to the needs of the times. In this research, the type of research used is library research. The data collection used is the documentation method. The research results show that the MBKM policy includes four main policies, namely: ease of opening new study programs, changes to the university accreditation system, ease of universities becoming legal entities, and the right to study for three semesters outside the study program. Learning activities outside the study program and outside college include internships, projects in villages, teaching at schools or madrasas, student exchanges, research, entrepreneurship, independent projects, and humanitarian projects. In general, there are three stages in curriculum development, namely the curriculum design stage, learning implementation, and learning evaluation.